Hyponatraemia-treatment standard 2024 - Spasovski, Goce (Oxford University Press (OUP), 2024)
Hyponatraemia is the most common electrolyte disorder in hospital patients associated with increased morbidity, mortality, hospital stay and financial burden. The speed of a correction with 3% sodium chloride as a 100- to 150-ml intravenous bolus or continuous infusion depends on the severity and persistence of the symptoms and needs frequent biochemical monitoring. The rapid intermittent administration of hypertonic saline is preferred for treatment of symptomatic hyponatraemia. In asymptomatic mild hyponatraemia, an adequate solute intake with an initial fluid restriction (FR) of 500 ml/day adjusted according to the serum sodium (sNa) levels is preferred. Almost half of the syndrome of inappropriate antidiuretic hormone (SIADH) patients do not respond to FR as first-line therapy. At present, urea and tolvaptan are considered the most effective second-line therapies in SIADH. However, the evidence for guidance on the choice of second-line therapy of hypotonic hyponatraemia is lacking. Oral urea is considered to be a very effective and safe treatment. Mild and asymptomatic hyponatraemia is treated with adequate solute intake (salt and protein) and initial FR with adjustments based on sNa levels. Specific treatment with vaptans may be considered in either euvolaemic or hypervolaemic patients with high ADH activity. In order to ensure optimal patient outcome, close monitoring and readiness for administration of either hypotonic fluids or desmopressin may be crucial in the decision-making process for specific treatment and eventual overcorrection consequences. According to the guidelines, gradual correction and clinical evaluation is preferable over rapid normalization of sNa towards the laboratory reference ranges.